(3ahGFO GdOGQS GdeTQaI Ydi Yjhf GdeLGdS aj abg GdeGdcjIs - (3eMeO Hf EHQGgje Hf NjQI, CHh GdbGSe Hf GdehGYjfj GdbQWHj GdETHjdj,J (B564 (3g` s
(3ChdgG (B:s
(3cJGH GdRcGI GNJda ai GTJbGb GdRcGI heYfGgG s
(3BNQgG (B:s
(3cJGH GdZVH hBNQ eG ajg(B: (3eSCdI GdMce Hjf Cgd GdPeI hbjd Efg ai GdJXGde s
(3HYV GdChQGb Ydi Qb ZRGds
(3HBNQgG SeGYGJ efbhdI ef GdCUd GdefJSN efgs
(3GdehLhO efg (B7 (3CLRGA (B: (3GdKGef (B_ (3GdKGfi YTQ (B_ (3GdKGdK YTQ (B_ (3GdNGeS hGdYTQhf GdNGeS hGdKdGKhf (B_ (3GdKGdK hGdCQHYhf (B_ (3GdNGeS hGdCQHYhfs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdeGdcjs